Correlation Between CD4 Level and The Severity of Pneumocystis Pneumonia in Patients with Human Immunodeficiency Virus at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar, Bali - Aries Hasan Basri; I Made Susila Utama (MEDICINUS, 2025)
Pneumocystis jirovecii is an opportunistic fungal pathogen that causes life-threatening cases of pneumocystis pneumonia (PCP) in immunodeficient patients. In patients with human immunodeficiency virus (HIV), the risk of developing PCP increases when the CD4 count <200 cells/μl. This study aimed to determine the correlation between the CD4 level and the degree of severity of pneumocystis pneumonia in HIV patients at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar, Bali. A retrospective analysis was conducted on HIV patients diagnosed with PCP between 2020 to 2022 period. The researchsubjects were all PCP-PCR positive patients who were hospitalized at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar. The results of the study showed a total of 120 subjects, including 28 (23.3%) male subjects with severe PCP and 11 (9.2%)female subjects with severe PCP. The highest number of cases was found in the age range ages 20‒40 years, with 20 (16.6%) subjects having severe PCP. Regarding treatment status, 23 (19.2%) subjects with severe PCP were pre-HAART(highly active antiretroviral therapy) while 16 (13.3%) subjects were on HAART. The highest proportion of severe PCP cases was found in subjects with a CD4 count of less than 50 cells/μl, totaling 32 subjects (26.6%). The Kruskal-Wallistest was applied to assess the association between the CD4 count categories and PCP severity in HIV patients. The study concluded that there is a significant correlation between CD4 levels and the severity of pneumocystis pneumonia in HIVpatientsat RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar.